Is The Unitary Competence Hypothesis Tenable? - Gunadi H. Sulistyo (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 1994)
In Oiler's view (1979) the idea that language can be broken down into smaller, isolated segments falls short of validity. Instead, Oller hypothesises the existence of a single faculty which is responsible for all language processing. Although his proposal is derived from several studies, this is not sufficient assurance for the validity of the theory he tries to establish.